The Impact of Geographical Indications on Sustainable Rural Development: Comprehensive Economic and Cultural Insights from Wayanad, Kerala - Jyothy Meenakshi K; Murshid CM; Rima Fathima (International Journal of Rural and Regional Development, 2025)
Geographical Indications (GIs) play a vital role in fostering sustainable rural development by linking unique local products to their geographic origins. This study explores the impact of GIs on economic growth, cultural preservation, and environmental sustainability in Wayanad, Kerala. Drawing from extensive secondary data and detailed case studies including Wayanad Coffee, Jeerakasala Rice, and traditional handicrafts, the research highlights how GI certification enhances market value, improves income levels, and preserves indigenous knowledge systems. These products have gained increased recognition in national and international markets, providing economic upliftment and livelihood support for local communities, particularly women and tribal populations. The study finds that GIs also strengthen cultural identity and encourage the continuation of traditional practices and eco-friendly production methods. Despite these benefits, several challenges persist, including high registration costs, limited awareness, and insufficient institutional support. These barriers often restrict the full participation of small-scale producers and reduce the potential impact of GIs. To overcome these hurdles, the study recommends a multi-stakeholder approach involving strong legal frameworks, government incentives, local-level awareness campaigns, and community-driven marketing strategies. Emphasis is also placed on the need for training, infrastructure development, and consistent policy support to maximize the developmental benefits of GIs. By combining traditional wisdom with modern value addition and protection mechanisms, GIs can act as a powerful tool for inclusive rural growth. This research ultimately underscores the transformative potential of GIs in revitalizing rural economies, safeguarding cultural heritage, and ensuring long-term community resilience through sustainable development models based on authenticity and regional uniqueness.
Keywords: Economic growth; Geographical indications; rural economy; sustainable development; wayanad